Agency Theory: Methodology, Analysis A Structured Approach to Writing Contracts - Stremitzer, Alexander (Forschungsergebnisse der Wirtschaftsuniversitaet Wien, 2018)
Designing a contract is often more of an economic than a legal problem. A good contract protects parties against opportunistic behavior while providing motivation to cooperate. This is where economics and, especially contract theory, may prove helpful by enhancing our understanding of incentive issues. The purpose of this book is to provide specific tools which will help to write better contracts in real world environments. Concentrating on moral hazard literature, this book derives a tentative checklist for drafting contracts. As an economic contribution to a field traditionally considered an art rather than a science, this treatment also gives much attention to methodological issues.